Performance Evaluation of Solid Desiccant Wheel Dehumidifier for Agricultural Crop Drying - Attkan, Arun Kumar; Raleng, Angam; Kumar, Nitin; Alam, M. S.; Yadav, Y. K. (International Journal of Bio-resource and Stress Management, 2016)
The performance of the rotary bed desiccant dehumidifier was evaluated for different air mass flow rates of 0.32, 0.63, 0.95 and 1.30 kg s-1 and different reactivation temperatures of 60, 70, 80, 90, 100, 110 and 120 °C, respectively. Obtained experimental data including temperature and absolute humidity at both process and reactivation side via random factorial scheme are analyzed. Comparison of data average is carried out with the help of the multi amplitude test of Tukey. Statistical analysis of experimental data shows that reactivation temperature (RT) and air mass flow rate (AMFR) have a reasonable impact on the process and reactivation out temperature and absolute humidity. However, a combined effect of reactivation temperature (RT) and air mass flow rate (AMFR) on process and reactivation out temperature and absolute humidity is not meaningful (p>0.05). Process air inlet moisture content affects outlet moisture, if air is more humid entering the dehumidifier, it will be more humid leaving the unit. More moisture is removed from the process air as inlet humidity ratio increases. Process air mass flow rate through the desiccant bed strongly affects leaving moisture. Outlet humidity ratio is less if process air flow rate is less. Thus, more moisture is removed when the air mass flow rate is less. Results shows that by controlling air mass flow rate and reactivation temperature, a good range of temperature can be attained which is suitable for drying of agricultural crops at low humidity. Low temperature food drying enhances the product quality, drying rate and retention of nutrients.